Program Keluarga Berencana Nasional Di Indonesia: Tinjauan Komparatif Antara Prinsip Maslahat Dalam Hukum Islam Dan Rekomendasi Kesehatan Masyarakat - Safrizal, Safrizal (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to comparatively analyze the principle of maslahat in Islamic law with the Family Planning Program (KB) as a form of community health regulation in Indonesia. Using a doctrinal legal methodology, this research examines relevant legal literature and doctrines to understand the similarities and differences between the two. The results show that both the principle of maslahat and the KB program aim to achieve societal welfare, albeit from different perspectives. The principle of maslahat in Islamic law has a broader scope and is normative in nature, while the KB program focuses more on reproductive health and is application-oriented. Both use a preventive approach and recognize the importance of social values in society. This research concludes that both can complement each other in efforts to improve the quality of life for Indonesians.